THE IMPACT OF ISLAMIC FINANCIAL DEVELOPMENT ON ENERGY INTENSITY: EVIDENCE FROM ISLAMIC BANKS - Abdul-Jalil Ibrahim; Nasim S. Shirazi; Amin Mohseni-Cheraghlou (Journal of Islamic Monetary Economics and Finance, 2021)
The relationship between financial development and energy intensity is yet to be firmly established as the literature is newly emerging, and the few empirical studies that have been conducted provide conflicting results. While some conclude that there is a U-shaped relationship between financial development and energy intensity, others show a linear relationship between the two variables. This study investigates the relationship between financial development and energy intensity by focusing on the role of Islamic financial development. It covers 30 countries where Islamic banks are present. Using the fixed-effects panel model, the empirical results suggest that Islamic banking development significantly increases energy intensity in the sample countries. We also identify other important factors that increase it. These include carbon emissions, renewable energy use and energy imports. The findings point to the importance of designing policies to incentivise Islamic banks and Shari'ah-compliant investors to finance clean energy technologies as a potent tool for reducing energy intensity, achieving sustainable development, and greening Islamic finance.